Combined delivery of a TGF-β inhibitor and an adenoviral vector expressing interleukin-12 potentiates cancer immunotherapy. (1st October 2017) - Jiang, Jiayu; Zhang, Yuandong; Peng, Ke; Wang, Qin; Hong, Xiaoyu; Li, Hanmei; Fan, Gerui; Zhang, Zhirong; Gong, Tao; Sun, Xun
Graphical abstract: Schematic representation of how β-cyclodextrin-PEI co-deliver TGF-β inhibitor and an adenoviral vector expressing interleukin-12 to tumor cells and trigger antitumor immune response. Abstract: Cancer immunotherapy appears to have a promising future, but it can be thwarted by secretion of immunosuppressive factors, such as transforming growth factor-β (TGF-β), which inhibits local immune responses to tumors. To weaken immune resistance of tumors and simultaneously strengthen immune responses, we developed a multifunctional polymer that could co-deliver hydrophobic TGF-β inhibitor and an adenovirus gene vector to tumor sites. This co-delivery system sustainably released TGF-β inhibitor SB-505124 and effectively transferred the adenovirus vector carrying the interleukin-12 gene. In addition, it significantly delayed growth of B16 melanoma xenografts in mice and increased animal survival. Mechanistic studies showed that this combination therapy enhanced anti-tumor immune response by activating CD4 + and CD8 + T cells, natural killer cells and interferon-γ secretion in the tumor microenvironment. Statement of Significance: To weaken immune resistance of tumors and simultaneously strengthen tumors' immune responses, we synthesized a structurally simple, low-toxic but functional polymer β-cyclodextrin-PEI to encapsulate a hydrophobic TGF-β inhibitor SB-505124 and to complex adenovirus vectors expressing IL-12. This is the first report demonstrating that combining TGF-β inhibitor with IL-12 could provide effective immunotherapy against melanoma by the sustainable release of SB-505124 and the effectible transduction of IL-12 gene in tumor cells. The rational delivery system presented a comprehensive and valued platform to be a candidate vector for co-delivering hydrophobic small-molecule drugs and therapeutic genes for treating cancer, providing a new approach for cancer immunotherapy.